Hybrid photometric redshifts for sources in the COSMOS and XMM-LSS fields. Issue 3 (15th April 2022) - Hatfield, P W; Jarvis, M J; Adams, N; Bowler, R A A; Häußler, B; Duncan, K J
ABSTRACT: In this paper, we present photometric redshifts for 2.7 million galaxies in the XMM-LSS and COSMOS fields, both with rich optical and near-infrared data from VISTA and HyperSuprimeCam. Both template fitting (using galaxy and active galactic nuclei templates within LePhare ) and machine learning (using gp z) methods are run on the aperture photometry of sources selected in the K s -band. The resulting predictions are then combined using a Hierarchical Bayesian model, to produce consensus photometric redshift point estimates and probability distribution functions that outperform each method individually. Our point estimates have a root mean square error of ∼0.08–0.09, and an outlier fraction of ∼3–4 percent when compared to spectroscopic redshifts. We also compare our results to the COSMOS2020 photometric redshifts, which contain fewer sources, but had access to a larger number of bands and greater wavelength coverage, finding that comparable photo- z quality can be achieved (for bright and intermediate luminosity sources where a direct comparison can be made). Our resulting redshifts represent the most accurate set of photometric redshifts (for a catalogue this large) for these deep multisquare degree multiwavelength fields to date.